Erianin: A phytoestrogen with therapeutic potential - Li, Gangmin; Zhang, Huiqiong; Lai, Hui; Liang, Gang; Huang, Jiang; Zhao, Fulan; Xie, Xiaofang; Peng, Cheng (Frontiers in Pharmacology, 2023)
Erianin, a phytoestrogen with therapeutic potential, is one of the major active components of Dendrobll caulis. Erianin has a variety of pharmacological effects, such as anti-tumor, antiinflammatory, anti-diabetic retinopathy, anti-psoriasis, and antibacterial effects. Especially, in regard to the anti-tumor effect of erianin, the underlying molecular mechanism has been partly clarified. In fact, the numerous pharmacological actions of erianin are complex and interrelated, mainly including ERK1/2, PI3K/Akt, JAK2/STAT3, HIF-1α/PD-L1, PPT1/mTOR, JNK/c-Jun, and p38 MAPK signal pathway. However, on account of the poor water solubility and the low bioavailability of erianin, greatly affected and limited its further development and application. And it is worthwhile and meaningful to explore more extensive pharmacological effects and mechanisms, clarify pharmacokinetics, and synthesize the derivatives of erianin. Conclusively, in this paper, the pharmacological effects of erianin and its mechanism, pharmacokinetics, and derivatives studies were reviewed, in order to provide a reference for the development and application of erianin.